How Do Family Responsible Ownership Practices Enhance Social Responsibility in Small and Medium Family Firms? - Aragon, Cristina; Iturrioz-Landart, Cristina (European Journal of Family Business, 2020)
This paper aims to measure the influence of the family responsible ownership practices on the socially responsible behaviour of family small and medium firms. To reach this purpose, we define six hypothesis and we apply an empirical testing of an integrative model. Based on a sample of 84 family SMEs, we use structural equation modelling to test for possible relationships within and between the constructs. This study reveals the relevance of the family responsible ownership practices as a driver that influences social responsible practices in family SMEs. The results confirmed that positive relationships exist between each of the following three antecedents: a) responsible management succession, b) responsible financial resource allocation and c) professionalism and social responsibility among family SMEs. Additionally, a positive relationship between family responsible ownership practices and family firm social responsibility was found.